2016
DOI: 10.1016/j.oraloncology.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-21 and microRNA-375 from oral cytology as biomarkers for oral tongue cancer detection

Abstract: Objective We previously performed a meta-analysis of microRNA profiling studies on head and neck / oral cancer (HNOC), and identified 11 consistently dysregulated microRNAs in HNOC. Here, we evaluate the diagnostic values of these microRNAs in oral tongue squamous cell carcinoma (OTSCC) using oral cytology samples. Materials and Methods The levels of 11 microRNAs were assessed in 39 oral cytology samples (19 OTSCC and 20 normal subjects), and 10 paired OTSCC and adjacent normal tissues. The predictive power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…For example, Kujan et al displayed high‐quality immunoreactivity for fragile histidine triad gene (FHIT) of oral epithelial cells from healthy subjects based on LBC slides. Other studies have shown promising results by testing DNA‐image cytometry using LBC samples collected by oral brushing . Further, the extraction of RNA from oral epithelial brush samples to detect early markers of oral carcinogenesis has also been recently investigated .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kujan et al displayed high‐quality immunoreactivity for fragile histidine triad gene (FHIT) of oral epithelial cells from healthy subjects based on LBC slides. Other studies have shown promising results by testing DNA‐image cytometry using LBC samples collected by oral brushing . Further, the extraction of RNA from oral epithelial brush samples to detect early markers of oral carcinogenesis has also been recently investigated .…”
Section: Discussionmentioning
confidence: 99%
“…20,35,47,69,75 Henson et al observed that downregulation of hsa-mir-100-5p is linked to heightened levels of proliferation and altered gene expression in OSCC cell lines. 20,35,47,69,75 Henson et al observed that downregulation of hsa-mir-100-5p is linked to heightened levels of proliferation and altered gene expression in OSCC cell lines.…”
Section: Hsa-mir-100-5pmentioning
confidence: 99%
“…In this scenario, improvement in patient's survival requires both early detection [7] as well as the possibility of predicting, at the moment of diagnosis, which patients will benefit from a specific treatment. Tailoring the treatment is of great importance and may help in the management of treatment planning and follow-up, improving survival rates.…”
Section: Introductionmentioning
confidence: 99%